DIAMOND OF THE DESERT: THE CASE OF QATAR’S 2022 FIFA WORLD CUP - Eduardo Russo (14427084) (2022)
For the first time in the Arab world, the FIFA World Cup in Qatar 2022 was one of the main drivers for promoting important infrastructural changes in the country, as well as for transforming the image of Qatar in order to make the destination more attractive to foreign tourists. However, despite the great wealth from its Oil & Gas reserves, several social challenges that historically affect the country began to emerge due to greater coverage of the international media, threatening the expectations of positive legacies left on the country's image from the event. Given this context, the case puts the reader in the role of Ahmed Al-Nasr, then Chairman of the Qatar Supreme Committee for Delivery and Legacy, as he faces different pressures made by major international brands sponsoring the event who now see their image threatened by successive controversies that the country has been involved in and they are threatening to withdraw their support and investments. The case is indicated for undergraduate and graduate students of courses in the area of Tourism, Sport Management, and Business interested in discussing topics and concepts related to environmental, social, and governance (ESG) responsibility, management of mega events, international marketing, and country destination image. Other Information Published in: Tourism and hospitality management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.20867/thm.28.2.12